The Relationship Between MMP17 Variants and Ischemic Stroke Risk in the Population from Shaanxi Province in China - Li W; Liu Y; Xu X; Zhang Q; Zhang X; Zhang J; Niu X; Yang S; Zhang X; Shi W; Zhang G; Chang M; et al. (Pharmacogenomics and Personalized Medicine, 2023)
Weiping Li, Yanqing Liu, Xiaoling Xu, Qi Zhang, Xiao Zhang, Jie Zhang, Xiaochen Niu, Shiyao Yang, Xiaobo Zhang, Wenzhen Shi, Gejuan Zhang, Mingze Chang, Ye Tian Xi’an Key Laboratory of Cardiovascular and Cerebrovascular Diseases, Xi’an No.3 Hospital, The Affiliated Hospital of Northwest University, School of Life Sciences and Medicine, Northwest University, Xi’an, Shaanxi Province, People’s Republic of ChinaCorrespondence: Ye Tian; Wenzhen Shi, Xi’an Key Laboratory of Cardiovascular and Cerebrovascular Diseases, No. 10, East Section of Fengcheng Third Road, Weiyang District, Xi’an, Shaanxi Province, People’s Republic of China, Tel +86 29-61816515, Email chhty@sina.com; shiwenzhen736@163.comBackground: Ischemic stroke (IS) was a multifactorial disease, which was the main cause of death and adult disability. Genetic factors cannot be ignored.Objective: The present study discussed the relationship between MMP17 variants and the susceptibility of IS.Methods: Based on the Agena MassARRAY platform, we genotyped single nucleotide polymorphisms (SNPs) on the MMP17 gene in 1345 participants (670 controls and 675 cases). We used logistic regression analysis to analyze the association of MMP17 SNPs with the risk of IS in the Chinese population, with odds ratio (OR) and 95% confidence intervals (CIs). False-positive report probability (FPRP) detected false positives on the significant results. Besides, we detected the SNP–SNP interaction to predict IS risk by multi-factor dimensionality reduction (MDR) analysis.Results: In the total analysis, MMP17 rs7975920 conferred an increased susceptibility to IS. After a stratified analysis by age and gender, the significant association between rs7975920 and IS risk was displayed in the subjects aged > 55 years old and females. After stratified analysis by smoking and drinking, MMP17 rs6598163 was related to the risk of IS in smokers and rs7975920 was associated with the risk of IS in smokers and was in correlation with IS risk in drinkers.Conclusion: In short, we first observed that MMP17 rs7975920 and rs6598163 were related to the risk of IS. The above results provided a theoretical basis for the elaboration of the role of MMP17 in IS in the Chinese population.Keywords: ischemic stroke, MMP17, single nucleotide polymorphisms, population